First records of the genus Hishimonus Ishihara from Thailand (Hemiptera: Cicadellidae: Deltocephalinae: Opsiini) including description of three new species - Dai, Wu; Fletcher, Murray J.; Zhang, Yalin (Zootaxa, 2013)
Seven species of Hishimonus Ishihara are recorded in Thailand, four of which were previously recorded from neighbour-ing countries and three new species described herein: Hishimonus pallidus sp. nov., H. diffractus sp. nov. and H. gillespiei sp. nov. The other four species are H. concavus Knight, previously known from the Philippines, H. subtilis Knight record-ed from Singapore, H. aberrans Knight recorded from Taiwan and H. phycitis (Distant), which is widespread in Asia from the Middle East to China. These species are all newly recorded from Thailand and represent the first records of the genus Hishimonus in that country.